2006
DOI: 10.1093/eurheartj/ehi720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 19 pre-operative risk stratification models in open-heart surgery

Abstract: EuroSCORE, Cleveland Clinic, and Magovern risk algorithms showed superior performance and accuracy in open-heart surgery, and EuroSCORE, NYS, and Cleveland Clinic in CABG-only surgery. Although the models were originally designed to predict early mortality, the 1-year mortality prediction was also reasonably accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
2
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(165 citation statements)
references
References 36 publications
2
151
2
10
Order By: Relevance
“…1 Current cardiac surgery risk stratification models weigh heavily towards patient characteristics and chronic conditions that are not amenable to optimization. [2][3][4] While diabetics are a high-risk group for early complication following cardiac surgery, [5][6][7] some have suggested that tight postoperative glycemic control may improve outcome, though this is somewhat controversial. [8][9][10][11][12] Monitoring glycosylated hemoglobin (hemoglobin A1c, HbA1c) is a recommended method for assessing the longterm effectiveness of diabetes therapies, 13 and it has prognostic value as well; 14 lower HbA1c levels are associated with better glycemic control, and they also predict reduced long-term complication rates, e.g., nephropathy and retinopathy, and forecast improved survival.…”
Section: Rèsumèmentioning
confidence: 99%
“…1 Current cardiac surgery risk stratification models weigh heavily towards patient characteristics and chronic conditions that are not amenable to optimization. [2][3][4] While diabetics are a high-risk group for early complication following cardiac surgery, [5][6][7] some have suggested that tight postoperative glycemic control may improve outcome, though this is somewhat controversial. [8][9][10][11][12] Monitoring glycosylated hemoglobin (hemoglobin A1c, HbA1c) is a recommended method for assessing the longterm effectiveness of diabetes therapies, 13 and it has prognostic value as well; 14 lower HbA1c levels are associated with better glycemic control, and they also predict reduced long-term complication rates, e.g., nephropathy and retinopathy, and forecast improved survival.…”
Section: Rèsumèmentioning
confidence: 99%
“…Several risk-scoring systems have been developed for patients undergoing cardiac surgery to predict mortality [28] and receiver operating characteristics (ROC) curves were used to describe the performance and accuracy of these scoring systems. Actual mortality was 2.9% at 30 days and 6.1% at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…В последнее время появились данные о том, что эта шкала "занижает" риск развития периоперационных осложнений. Аддитивная и логистическая шкалы EuroSCORE про-демонстрировали надежность при прогнозировании риска госпитальной летальности после коронарного шунтирования [4]. Одним из достоинств этой про-гностической системы является учет в шкале отяго-щающих предоперационных факторов риска, в том числе наличие повышенного уровня креатинина -выше 200 мкмоль/л [4,5].…”
Section: Discussionunclassified
“…Кроме того, эта шкала про-ста в подсчете баллов. В последнее время появился ряд статей, указывающих на высокий процент лож-ных результатов прогноза [4]. В настоящее время ведутся дискуссии о модификации шкалы либо созда-нии принципиально иных шкал, основанных на использовании высокочувствительных биологиче-ских маркеров, способных прогнозировать еще в до операционном периоде развитие неблагоприят-ных сердечно-сосудистых, почечных и других ослож-нений.…”
Section: Discussionunclassified